A Study of Technology Product Advertising Subtitle Translation Under Communicative Translation Theory: A Case Study of Samsung Galaxy Z-Fold2 Review - Lu, Bianmutong (Journal of Theory and Practice in Linguistics, 2025)
Evaluation videos of technological products have emerged as a primary medium for audiences to comprehend diverse devices, consequently endowing such content with an inherent promotional nature. To facilitate Chinese viewers’ understanding of international tech products, the optimization of subtitle translation has become a critical undertaking. Guided by the communicative translation theory, this paper examines translation strategies for promotional subtitles of technological products through a case study of the E-C subtitle translation for Samsung Galaxy Z-Fold2 Review from the Android Central channel on YouTube. Key strategies including transcreation, supplementation, and non-translation are systematically explored, with subsequent analysis of their practical efficacy in cross-cultural communication. The study aims to provide methodological references for enhancing the accessibility and marketing effectiveness of global tech products in localized contexts.